2021
DOI: 10.1109/access.2021.3110873
|View full text |Cite
|
Sign up to set email alerts
|

LoRa IoT-Based Architecture for Advanced Metering Infrastructure in Residential Smart Grid

Abstract: Internet of Things (IoT) technologies are opening new opportunities and services for different smart grid applications such as advanced meter infrastructures (AMI), distributed energy resources, and electric vehicles. Among these applications, AMIs represent the first step toward future smart grid implementation by enabling the reading and recording of electric power consumption on request or a schedule. In this study, the main focus is designing an IoT-based architecture to support AMIs' daily reporting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Thus, a significant amount of concentrators could be removed from the smart metering infrastructure, inducing a significant reduction in energy consumption. Recent studies have shown the suitability of such long range wireless communication in a smart grid context, as presented in [30]. However, shifting from one communication technology to another implies a replacement of the current infrastructure, thus inducing gray energy consumption, in addition to installation costs for the grid operator.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a significant amount of concentrators could be removed from the smart metering infrastructure, inducing a significant reduction in energy consumption. Recent studies have shown the suitability of such long range wireless communication in a smart grid context, as presented in [30]. However, shifting from one communication technology to another implies a replacement of the current infrastructure, thus inducing gray energy consumption, in addition to installation costs for the grid operator.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated home automation systems that utilise multiple communication technologies such as LoRaWAN, server-based LoRa gateways, and Bluetooth connectivity to control different types of appliances were proposed by [ 26 ]. IoT-based AMI daily reporting and billing in a residential grid using LoRa technology were designed by [ 27 ]. A new two-hop implementation of the LoRa WAN LEACH protocol (LLP) was proposed by [ 28 ] using the LEACH algorithm to optimise the throughput and power dissipation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As another smart grid application, but from a different viewpoint, a LoRaWAN communication system was evaluated for monitoring residential consumption, billing, and scheduling purposes. In this case, an advanced metering infrastructure (AMI) was proposed based on using LoRaWAN protocol and performance aspects, such as packet deliver ratio (PDR), packet collisions, throughput, and transmission power consumption were evaluated by simulations [39].…”
Section: Review Of Lorawan and Lora Applications In Smart Systemsmentioning
confidence: 99%